A Novel VNA-Enhanced Technique for Ka-Band Insertion Loss Measurement in Microstrip Lines - Ching-Wen Tang; Wei-Lun Tsai; Chieh Lee; You-Lin Luo (IEEE Access)
A novel measurement technique has been developed to enhance the accuracy of insertion loss measurements using vector network analyzers (VNAs), addressing the challenge of data fluctuations — a critical factor in determining circuit bandwidth and ensuring high-frequency signal integrity. The proposed method employs a Point-wise Least Squares (PLS) approach, eliminating the need for manual selection of smoothing bandwidth and simplifying the measurement process with a dedicated flowchart. This technique accurately differentiates insertion loss variations in microstrip lines, even across the Ka-band frequency range, ensuring reliable and consistent data by reducing deviations, particularly at band edges. The improved measurement accuracy supports the design and optimization of high-performance communication systems.